Pengaruh Teknik Relaksasi Benson terhadap Tingkat Nyeri Dada pada Pasien Sindrom Koroner Akut (SKA) Pasca Tindakan PCI di Instalasi Gawat Darurat (IGD) - Muchammad Hasyim Asy’ari; Indah Sri Wahyuningsih; Suyanto Suyanto (Journal of Health, Medical, and Psychological Studies, 2026)
Patients with Acute Coronary Syndrome (ACS) post Percutaneous Coronary Intervention (PCI) often still experience chest pain due to inflammatory processes or psychological factors. Unmanaged pain can increase cardiac workload. The Benson relaxation technique is a non-pharmacological intervention that combines deep breathing techniques with an element of faith (spiritual) to induce a relaxation response. This study aims to determine the effect of the Benson relaxation technique on reducing chest pain levels in ACS patients after PCI at Referral hospitals in Central Java Province. This study used a one-group pretest-posttest design with a sample of 36 respondents selected by purposive sampling. Pain measurement used the Numeric Rating Scale (NRS) before and after the intervention. The Benson relaxation technique was administered for 10–15 minutes per session. Data analysis used the Wilcoxon Signed Ranks Test.Before the intervention, all respondents (100%) experienced moderate chest pain (mean=5.11). After the intervention, there was a significant reduction, with 61.1% of respondents falling into the mild pain category and 38.9% remaining in the moderate category (mean=3.39). Statistical test results showed a significant difference between pain scores before and after the intervention (Z=-5.500; p=0.000).The Benson relaxation technique is proven effective in reducing chest pain levels in ACS patients post PCI in the Emergency Department